Введение в историю русской культуры: учебное пособие для вузов / И.В. Кондаков - Кондаков Игорь Вадимович (Аспект Пресс, 1997)
Экземпляры: (20160301) / Инвентарный номер: 34660 / Цена: / Сис.шифр: 63.3(2Р) / Авт.знак: К64 / ГРНТИ: 03.19 / ББК: 63.3(2Р)-7 я73